2021
DOI: 10.1186/s12913-021-06692-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the impact of two national health and social care integration programmes on emergency hospital admissions

Abstract: Background Policy-makers expect that integration of health and social care will improve user and carer experience and reduce avoidable hospital use. [We] evaluate the impact on emergency hospital admissions of two large nationally-initiated service integration programmes in England: the Pioneer (November 2013 to March 2018) and Vanguard (January 2015 to March 2018) programmes. The latter had far greater financial and expert support from central agencies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…There is some evidence that sites that took part in both the Pioneer and Vanguard programmes were able to make more sustained reductions in the growth of unplanned admissions [19]. It is also notable that a longer-term evaluation of one Vanguard site found that a lower rate of increase in a range of measures of unplanned hospital care towards the end of a six-year period of pilot operation.…”
Section: What Did the Pilot Programmes Achieve?mentioning
confidence: 99%
“…There is some evidence that sites that took part in both the Pioneer and Vanguard programmes were able to make more sustained reductions in the growth of unplanned admissions [19]. It is also notable that a longer-term evaluation of one Vanguard site found that a lower rate of increase in a range of measures of unplanned hospital care towards the end of a six-year period of pilot operation.…”
Section: What Did the Pilot Programmes Achieve?mentioning
confidence: 99%
“…This was deemed especially important given that new ways of working were not always reported to result in immediately tangible benefits to participants. Evaluations of integrated care approaches in different settings have demonstrated that evidence of impact at population level is likely to be seen only after several years following implementation [30,31]. Supporting local innovation requires enduring commitment and long-lasting mandates to provide greater certainty over longer time-scales.…”
Section: Discussionmentioning
confidence: 99%
“…Recent policies have hoped that improving the integration of health and social care should reduce demand for emergency care services and unnecessary hospitalizations. During the last decade, the Integrated Care and Support Pioneer programmes and the Vanguards sites (Morciano et al., 2021) are two large national integration care initiatives in the NHS in England. In 2013, the Integrated Care and Support Pioneer program promoted horizontal integration between the local health and social care systems by encouraging the implementation of new ways of working together.…”
Section: Background On the English Healthcare System And Sicpmentioning
confidence: 99%